To solve the equation 6y - 6 = 4y + 16, we need to isolate the variable y on one side of the equation.
First, let's subtract 4y from both sides:
6y - 4y - 6 = 4y + 16 - 4y
Simplifying this equation gives us:
2y - 6 = 16
Next, let's add 6 to both sides:
2y - 6 + 6 = 16 + 6
Simplifying this equation gives us:
2y = 22
Finally, let's divide both sides by 2 to solve for y:
2y/2 = 22/2
Simplifying this equation gives us:
y = 11
Therefore, the solution is y = 11.
6y – 6 = 4y + 16
(1 point)
Responses
y = 2.2
y = 2.2
y = –2.2
y = –2.2
y = 11
y = 11
y = 5
1 answer